Survey Effect of Exposure to Formaldehyde on Pulmonary Function Test in Hospital Staffs - Dehaghi, Behzad Fouladi (Asian Journal of Pharmaceutics (AJP), 2018)
Background and Aim: Air pollutants such as formaldehyde can affect lung functions and make distortion in gas changing of lungs. The volumes and the flows of each breath can be measured with spirometer test. The aim of this study was to assess the effects of formaldehyde exposure on the pulmonary function test in hospital staffs. Material and Methods: This cross-sectional study was conducted in a hospital and involving 60 participants (30 staffs in exposed group and 30 staffs in control group). The measurement of formaldehyde concentration was using method 3500 national institute for occupational safety and health. In this study, a questionnaire was used to evaluate and determine the prevalence of respiratory symptoms. Spirometry test was used to evaluate the parameters of pulmonary function in two groups. t-tests and Chi-square as statistics tests were used to create data analysis. Results: The respiratory symptoms showed a significant difference between exposed group and control group (P < 0.05). Furthermore, parameters of pulmonary function forced vital capacity, forced expiratory volume in the first second, and peak expiratory flow in the exposed group and the control group were significantly different (P < 0.05). Conclusion: Our study showed that exposed group with formalin has complex disorder of both restrictive and obstructive types.